The Permanent Value of the Primitive Christian Eschatology - Grant, Frederick C. (The biblical world, 1917)
Unless all signs fail the most marked issue of the next few years in our evangelical theology will be eschatology. And back of our view of the meaning of eschatology will be our attitude toward the Scriptures. Here the issue is, as much as anything, one of method. How are we to gain the everlasting gospel from current conceptions of what that gospel is? This is a real task, worthy of real thinking. We may well pray that in our efforts to get at the heart of the gospel we shall be free from temptation to harsh judgments of others, and particularly of such rhetorical descriptions of their views as may do them injustice. Believing as we do that eschatalogical pictures of the early church are symbols rather than realities, we also believe that the truths they represent are of the utmost importance for anyone who would understand the Christian religion.